If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 11 = 8 Reorder the terms: 11 + 3y = 8 Solving 11 + 3y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 3y = 8 + -11 Combine like terms: 11 + -11 = 0 0 + 3y = 8 + -11 3y = 8 + -11 Combine like terms: 8 + -11 = -3 3y = -3 Divide each side by '3'. y = -1 Simplifying y = -1
| 14=-16t^2+100 | | 5/6x=-1/12 | | (3x-4)(3x-8)= | | 3d=17.4 | | 7(3-6r)=357 | | 18.5=3n-1 | | 3x+18=18+9x | | 4.8=1.8-0.4y | | 3b+7-b=23 | | 2x-5=-7x+10 | | 20-2(n)=30-3(n) | | x/7-2=3/14 | | -2(4-7p)=-92 | | 22x-4-14x=2(4x-4)+4 | | 12q-6=8q+14 | | [40x^22y^11/20x^11y^22]^2 | | 2x+3+5x=-9-4x+2x | | 14-1/6n=1/6n-1 | | 2.7=2n-4 | | -0.5x+0.9x=51 | | 16-n=5(n)+4 | | g(5)=64(0.5(5)) | | 19=3c+1 | | 8x-6-2x=10+4x | | x^3-x^2-x+20=0 | | 7.1=2.6-0.7y | | 7x-30=5x-14 | | 10x-3=8x+16 | | 3w-3(w-5)=22 | | 7x-30=5x-15 | | 1+8(n)=12(n)-15 | | 7x+4=x+1 |